Optical light curves of FUor and FUor-like objects. Issue Volume 12:Issue S325(2016) (30th May 2017) - Semkov, Evgeni; Peneva, Stoyanka; Ibryamov, Sunay
Abstract: Using recent data from photometric monitoring and data from the photographic plate archives we aim to study, the long-term photometric behavior of FUors. The construction of the historical light curves of FUors could be very important for determining the beginning of the outburst, the time to reach the maximum light, the rate of increase and decrease in brightness, the pre-outburst variability of the star. Our CCD photometric observations were performed with the telescopes of the Rozhen (Bulgaria) and Skinakas (Crete, Greece) observatories. Most suitable for long-term photometric study are the plate archives of the big Schmidt telescopes, as the telescopes at Kiso Observatory, Asiago Observatory, Palomar Observatory and others. In comparing our results with light curves of the well-studied FUors, we conclude that every new FUor object shows different photometric behavior. Each known FUor has a different rate of increase and decrease in brightness and a different light curve shape.